Evaluation of the relationship between facial growth pattern and buccal corridors in patients with skeletal class I malocclusion - خليل, فادي; تيزيني, محمد; خضر, يوسف (Latakia University Journal -Medical Sciences Series, 2021)
The relationship between the growth pattern and the buccal corridors was studied to benefit from this relationship in the diagnostic records. Aims: To investigate the existence of a correlation between the facial growth pattern on the relationship between the form of the dental arch and the buccal corridors. Materials and methods: The study included 108 patients between (17-25) years. Lateral cephalometric radiographs and dental casts were taken and photographs were made. To determine the growth pattern, Audaxceph was used to analyze the radiographs of the participants in the research and to determinate the width of the buccal corridors by making measurements on the images using Adobe® Photoshop program. Results: In order to determine the location of the difference between the averages of the three patterns after conducting the ANOVA One-Way analysis of variance, and the importance of the differences, the (LSD) test was applied for the dimensional comparisons. Where the study confirmed that the difference was substantial between the average width of the buccal corridors between the vertical and normal growth patterns at a level of significance of 5%.